Penilaian kasus kegagalan pengobatan kloroquin terhadap penderita malaria falciparum dan faktor yang mempengaruhinya di beberapa puskesmas - Maryatul Soesanto Tjokrosonto, Mustofa (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Sabang is one of endemic malaria areas in Nanggroe Aceh Darussalam (NAD) Province. The first in-vitro resistance case to chloroquine was reported in 1983 and the in-vivo resistance case in the level of RII was also observed in 1983. Chloroquine is still used as the first line drug in the malaria control programmed at Sabang. The aim of this study is to evaluate the level of treatment failure of chloroquine to falciparum malaria and to analyze the risk factors associated to affect its failure in Sabang. Method: This study was an in-vivo test for 28 days using the protocol from WHO 2003. The protocol is used to assess the efficacy of chloroquine in uncomplicated falciparum malaria treatment, based on clinical and parasitological examination. The study was implemented in the General Hospital of Sabang and Puskesmas Paya Seunara region, during January – July 2004. The subjects are patient of malaria with mono infection of P. falciparum and include in inclusion criteria. In order to investigate the risk factors of the treatment failure, observational case control design was used. Result and conclusion: The result shows that: 62,14% adequate clinical and parasitological response (ACPR), 10,68% early treatment failure (ETF), 14,56% late clinical failure (LCF), and 12,62% late parasitological failure (LPF). on 14th day evaluation. Evaluation on 28th day shows that: 52,43% ACPR, 10,68% ETF, 20,39% LCF and 16,5% LPF. The risk factors that have significant relationship with treatment failure are splenomegaly (OR=6,06; 95%C1=1,86)